Evaluasi Pertumbuhan dan Hasil Beberapa Kultivar Kubis Bunga (Brassica oleracea var. botrytis L) Dataran Rendah pada Sistem Hidroponik Nutrient Film Technique - Umi Listiana; Rizka Novi Sesanti; Desi Maulida; Raida Kartina; Sekar Utami Putri; Betari Safitri (Politeknik Negeri Lampung, 2023)
The hydroponic system in a greenhouse for cauliflower cultivation can be a solution to the problem of conventional cultivation, but its needed for the cultivars that are most suitable for hydroponic systems, especially the Nutrient Film Technique (NFT) system. This study aims to (1) evaluate the growth and production yields of several cultivars of cauliflower in the Nutrient Film Technique (NFT) hydroponic system, (2) the best cultivar for cultivation of NFT hydroponic method. This study used a lowland cauliflower cultivars, namely PM 126, Mona, Diamond 40, Orient, and Pertiwi with 5 times. The data obtained from each observation variable were analyzed by means of analysis of variance which was carried out with a follow-up test with Honest Significant Differences (BNJ) at the 5% level. The results showed that cauliflower cultivars had different growth responses to the NFT system. Pertiwi cultivar had the best plant height compared to other cultivars, while the variables of leaf width, leaf length, time of flower emergence, flower weight, flower diameter and root length between cultivars showed no significant difference. The cultivar that shows good production results and is suitable for NFT hydroponic systems is PM126.